Efektivitas Strategi Promosi Terhadap Jumlah Pendaftar Program Studi Pendidikan Matematika Angkatan 2025 - Badriyah, Fitriyatul; Supriyo, Supriyo (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to describe the effectiveness of promotional strategies on the number of applicants for the Mathematics Education Study Programme at PGRI Wiranegara University (UNIWARA) Pasuruan for the 2025 intake. The study uses a quantitative approach with a descriptive design. Data were collected through a closed-ended questionnaire using a four-point Likert scale and interviews with the Head of the Study Programme as supporting data. Data analysis was performed using descriptive statistics in the form of frequency, percentage, and mean values. The results showed that social media was the most effective promotional strategy in attracting prospective students, as indicated by the mean value in the very effective category. The promotional information was considered clear, interesting, and helpful for prospective students in understanding the advantages and prospects of graduates of the Mathematics Education Study Programme. However, the frequency and intensity of promotion were considered suboptimal. The interview results revealed that the effectiveness of the promotion carried out only reached around 30–40 per cent, as reflected in the limited number of applicants. In addition to formal promotion, the informal role of students and alumni also contributed to attracting prospective students. These findings indicate that the promotion strategy needs to be improved through more focused and sustainable planning